2013
DOI: 10.1242/jeb.080556
|View full text |Cite
|
Sign up to set email alerts
|

Variation in temperature tolerance among families of Atlantic salmon (Salmo salar) is associated with hypoxia tolerance, ventricle size and myoglobin level

Abstract: SUMMARYIn fishes, performance failure at high temperature is thought to be due to a limitation on oxygen delivery (the theory of oxygen and capacity limited thermal tolerance, OCLTT), which suggests that thermal tolerance and hypoxia tolerance might be functionally associated. Here we examined variation in temperature and hypoxia tolerance among 41 families of Atlantic salmon (Salmo salar), which allowed us to evaluate the association between these two traits. Both temperature and hypoxia tolerance varied sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(136 citation statements)
references
References 56 publications
5
119
3
1
Order By: Relevance
“…For our experiment where DO was decreased at 0.33% min 21 , this represents a difference in mean time to LOE of ∼2.4 min. Such a difference may be negligible because the median time to LOE can vary substantially (up to 114.8 min) between families of Atlantic salmon (Anttila et al 2013). Thus, it is unclear what real-world impacts an effect of such small magnitude would have on fish performance and survival, given the spatial and temporal DO variability often experienced in wild and aquaculture environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For our experiment where DO was decreased at 0.33% min 21 , this represents a difference in mean time to LOE of ∼2.4 min. Such a difference may be negligible because the median time to LOE can vary substantially (up to 114.8 min) between families of Atlantic salmon (Anttila et al 2013). Thus, it is unclear what real-world impacts an effect of such small magnitude would have on fish performance and survival, given the spatial and temporal DO variability often experienced in wild and aquaculture environments.…”
Section: Discussionmentioning
confidence: 99%
“…Four half-sibling Atlantic salmon families were created by fertilizing eggs from four females with milt from one male, using captive-bred broodstock reared in freshwater at SALTAS. Half-sibling families were used to reduce potential variability in metabolic measurements and hypoxia tolerance between families (Anttila et al 2013). Fertilized eggs were randomly allocated to two replicate mesh isolation baskets (18 cm # 14.5 cm # 5.5 cm) per treatment, with each replicate incubated in separate Heath trays (39 cm # 32 cm # 5.5 cm; Marisource).…”
Section: Embryonic and Larval Incubationmentioning
confidence: 99%
“…Thus, because both T max and T arr were similar between populations, cardiac collapse near T crit would be more precipitous in the southern than in the northern population given the larger difference between T arr and T AB for the northern population. Unexplored here, but still needed, is a consideration of transgenerational changes in temperature tolerance (exposure of parental fish to adverse temperatures providing benefits to offspring) and heritability of thermal tolerance, which can occur in fishes 2,24 . Thus, natural selection has the potential to improve thermal tolerance in Atlantic salmon beyond the demonstrated benefits of high thermal plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…A switch from aerobic to anaerobic metabolism occurs in fish as temperatures approach their CT max [16], typical of animals experiencing hypoxic conditions. Indeed, CT max and hypoxia tolerance are positively correlated among families of Atlantic salmon (Salmo salar) [40], suggesting a genetic basis for anaerobic capacity. We found that juvenile chinook salmon reach their maximum heart rate (i.e.…”
Section: Discussionmentioning
confidence: 99%